Beware the source text: five (re)translations of the same work, but from different source texts - Ivaska, Laura; Huuhtanen, Suvi (Meta, 2020)
Source text (ST), although a central concept in translation studies, has remained vaguely defined. This complicates the identification of a translation’s ST, which in turn creates problems for research. Associating translations with the incorrect ST(s) leads to questionable conclusions and categorizations, especially when dealing with the types of translation that are defined and theorized with reference to their relationship with their ST(s), such as retranslation, indirect translation, pseudotranslation and self-translation. Our case study of five Finnish translations of Jules Verne’s Vingt mille lieues sous les mer demonstrates that these assumed retranslations have different STs. We adopt the notions of work and text to establish the relationships among the translations and STs involved: texts are representations of a work, and a work, in turn, is a literary creation implied by its various texts. Although the five Finnish translations have different source texts, they are all – as are their STs – texts of the same work. In other words, if source text is understood to be a text, the five translations are not, strictly speaking, retranslations; however, if source text is understood to be a work, then they are all retranslations of the same work. Therefore, the categorization of these translations – and thus also the points of view from which they can be studied – depends on whether source text is defined as a text or as a work.